Palynofacies Analysis of Subathu Sediments of Dogadda Area, Pauri-Garhwal District, Uttarakhand: Implications for Depositional Environment: A palynofacies analysis of Subathu sediments: Examining the deposition environment in Dogadda area, Pauri-Garhwal District, Uttarakhand (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Palynofacies analysis has been carried out on samples collected from Subathu Formation exposed along Umreila-Aeta road near Aeta village, Dogadda, Pauri- Garhwal District, Uttarakhand, India. Palynofacies analysis shows overall dominance of Grey amorphous organic matter followed by Fungal debris, Opaque phytoclasts, Cuticles, SporesPollen and Resin. The present lithological investigated section is made up of alternate layers of Purple and Green shales. The frequency variation pattern of dispersed organic matter and lithology indicates fluctuations from Fluvial to Shallow open marine environment for the deposition of the Subathu Formation in the area.